1998
DOI: 10.1111/j.1442-2026.1998.tb00486.x
|View full text |Cite
|
Sign up to set email alerts
|

Outcome from prehospital cardiac arrest in Melbourne, Australia

Abstract: Although the incidence and outcome of prehospital cardiac arrest have been reported for many cities, relatively few have originated from Australia. This study reviewed ambulance and hospital records of all patients who were in cardiac arrest when first attended by ambulance officers in metropolitan Melbourne between 1 February and 31 July 1995. Of 361 patients with a presumed primary cardiac cause of arrest, 113 (31%) were initially in ventricular fibrillation. The average ambulance response time was 9.4 minut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
14
1
1

Year Published

1998
1998
2016
2016

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(16 citation statements)
references
References 22 publications
0
14
1
1
Order By: Relevance
“…Çeşitli çalışmalarda öğrenim düzeyi yükseldikçe ilk yardım bilgi puanlarının da yükseldiği saptanmıştır (13,14).…”
Section: Discussionunclassified
“…Çeşitli çalışmalarda öğrenim düzeyi yükseldikçe ilk yardım bilgi puanlarının da yükseldiği saptanmıştır (13,14).…”
Section: Discussionunclassified
“…Out‐of‐hospital cardiac arrest is a major cause of death worldwide with an incidence of between 36 and 128 per 100 000 per year [5]. Reported survival rates range from < 5% to 35%[6, 7]. Successful resuscitation requires a co‐ordinated sequence of activities that include early activation of emergency services, early bystander cardiopulmonary resuscitation (CPR), rapid defibrillation, early advanced cardiac life support and early post‐resuscitation care.…”
Section: Discussionmentioning
confidence: 99%
“…It is now three decades since Pantridge demonstrated that out of hospital defibrillation could prevent sudden cardiac death in the community 1 . The report by Bernard in this issue of Emergency Medicine 2 , describes a system with a low survival rate post cardiac arrest and reinforces the fact that sudden cardiac death remains the biggest cause of preventable death in at least one major metropolitan area of Australasia. The American Heart Association has promoted the concept of a “chain of survival” to explain the systemic changes necessary to improve survival from cardiac arrest 3 .…”
mentioning
confidence: 93%